Measuring children's emotional and behavioural problems: are SDQ parent reports from native and immigrant parents comparable? - Ronja A. Runge; Renate Soellner (BMC, 2019)
Abstract Background The number of immigrants worldwide is growing and migration might be a risk factor for the mental health of children. A reliable instrument is needed to measure immigrants' childrens mental health. The aim of the study was to test the measurement invariance of the parent version of the Strengths and Difficulties Questionnaire (SDQ) between German native, Turkish origin and Russian origin immigrant parents in Germany. The SDQ is one of the most frequently used screening instruments for mental health disorders in children. Methods Differential Item Functioning (DIF) was tested in samples matched by socio-economic status, age and gender of the child. A logistic regression/item response theory hybrid method and a multiple indicators- multiple causes model (MIMIC) was used to test for DIF. Multi Group Confirmatory Factor analysis (MGCFA) was used to test for configural invariance. Parent reports of 10610 German native, 534 Russian origin and 668 Turkish origin parents of children aged 3-17 years were analysed. Results DIF items were found in both groups and with both methods. We did not find an adequate fit of the original five factor model of the SDQ for the Turkish origin group, but for the Russian origin group. An analysis of functional equivalence indicated that the SDQ is equally useful for the screening of mental health disorders in all three groups. Conclusion Using the SDQ in order to compare the parent reports of native and immigrant parents should be done cautiously. Thus, the use of the SDQ in epidemiological studies and for prevention planning is questionable. However, the SDQ turns out to be a valid instrument for screening purposes in parents of native and immigrant children.